2015
DOI: 10.11646/bde.37.2.1
|View full text |Cite
|
Sign up to set email alerts
|

<p><strong>Additions to the moss flora of Imbak Canyon Conservation Area, Malaysian Borneo</strong></p>

Abstract: Based on past and present collections, a total of 191 taxa in 68 genera of mosses are known to occur in Imbak Canyon Conservation Area in Malaysian Borneo. Out of these, 62 species in 37 genera and 19 families are reported here as new for the canyon. Leucobryum sericeum Broth. ex Geh., Papillidiopsis complanata (Dixon) W.R.Buck & B.C.Tan and Syrrhopodon scalariformis Dixon are reported as new to Sabah and Fissidens laxitextus Broth. ex Gangulee as new to Borneo

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 90%
“…The species richness of mosses in the study area is very high; 40% of the total of 766 species and infra-specific taxa reported from Borneo and 47% of the total of 651 species and infra-specific taxa reported from Sabah (Andi and Suleiman 2005, Suleiman et al 2006, 2009, 2011a, 2011b, 2017, Suleiman and Akiyama 2007, Higuchi et al 2008, Akiyama 2010, Ho et al 2010, Ellis et al 2010, 2015, 2016a, 2016b, Andi et al 2015, Chua and Suleiman 2015, Mohamed et al 2010, Suleiman and Rimi 2016). …”
Section: Resultsmentioning
confidence: 90%
“…Borneo is a huge island and only a small fraction of its land mass has been bryologically explored. Thus, the probability of finding newly recorded as well as undescribed species of bryophytes is still high (Akiyama and Suleiman 2015;Andi et al 2015;Chua and Suleiman 2015;Ellis et al 2015Ellis et al , 2016aEllis et al , 2016bEllis et al , 2018Ellis et al , 2019Zhu et al 2017;. With the four new additions of pleurocarpous mosses, Borneo now has 773 species and infraspecific taxa of mosses.…”
Section: Discussionmentioning
confidence: 99%
“…Heath forests have low, densely packed, and even canopy surfaces with little vertical stratification (Jucker et al 2018). The forest ground is well illuminated because of the smaller leaves that allow higher light penetration, resulting in high juvenile survivorship of shade-tolerant species and lightdemanding climax species, dense undergrowth, and high abundances of bryophytes, myrmecophytes, and insectivorous plants (Whitmore 1984;Proctor 1999;Ashton 2014;Chua and Suleiman 2015;Aiba and Kitayama 2020;Mansur et al 2021).…”
Section: Structure and Physiognomy Of Bornean Heath Forestsmentioning
confidence: 99%